STRATEGY FOR IMPROVING AKHLAKUL KARIMAH LEARNING THROUGH THE DISCOVERY LEARNING METHOD FOR EIGHTH GRADE STUDENTS AT MTSN 5 BANTUL - Zumaratul Azka; Nur Saidah (SOSIOEDUKASI, 2026)
This research is motivated by the importance of developing effective and efficient learning models in shaping students’ character based on Islamic values. The education of akhlakul karimah (noble character) is a fundamental aspect of the educational process; therefore, learning strategies that actively and meaningfully engage students are highly needed. The purpose of this study is to analyze the strategy of teaching akhlakul karimah through the implementation of the Discovery Learning method at MTsN 5 Bantul. This study employs a qualitative approach with data collection techniques including interviews, observations, and documentation to obtain comprehensive and in-depth data. The findings reveal that the implementation of the Discovery Learning method in teaching akhlakul karimah is effective in improving students’ understanding of noble moral values. Through learning stages such as exploration, observation, discussion, and reflection, students are encouraged to think critically, actively, and independently in discovering and understanding moral concepts. In addition, this method creates an interactive and conducive learning environment and strengthens positive relationships between teachers and students. Therefore, the learning of akhlakul karimah becomes more meaningful and contributes optimally to students’ character development.